Volta às fontes batismais: Celso Furtado e a profecia da Sudene - Barboza, Darlan Praxedes; Ribas, Elisabete Marin [UNESP] (Instituto de Estudos Brasileiros, 2021)
Resorting to selected documents from Celso Furtado’s personal archive donated to the Instituto de Estudos Brasileiros (IEB) in 2019, this article’s goal is to present and discuss two aspects concerning Furtados’s professional career: his work on the creation and administration of Sudene and the role he had as a teacher and inspiration model for the youth of the period. We hope that this short presentation may encourage other researchers to be interested in Celso Furtado’s archive - a collection composed by thousands of documents expressing a life and an intellectual production devoted to think and transform Brazil as a nation.

O presente artigo pretende ilustrar e discutir, a partir de documentos selecionados do arquivo pessoal de Celso Furtado, doado em 2019 ao Instituto de Estudos Brasileiros (IEB), duas facetas da trajetória profissional de seu titular: a atuação no contexto da criação e da gestão da Sudene e o papel que teve como formador e inspirador da juventude de sua época. Espera-se que esta breve exposição estimule o interesse de outros pesquisadores pelo acervo de Celso Furtado, composto de milhares de itens que exprimem uma vida e uma obra dedicadas a pensar e transformar o Brasil.
Back to baptismal fonts: Celso Furtado and Sudene’s prophecy
Keywords: Celso Furtado; Sudene; IEB; personal archive; Celso Furtado; Sudene; IEB; arquivos pessoais